Hypomethylation and Activation of Syncytin-1 Gene in Endometriotic Tissue - Zhou, Hongyuan; Li, Jinping; C. Podratz, Karl; Tipton, Tracy; Marzolf, Susan; Bin Chen, Hai; Jiang, Shi-Wen (Current Pharmaceutical Design, 2014)
Syncytin-1 plays a critical role in the maintenance of normal pregnancy by mediating the formation of syncytiotrophoblasts through a fosugenic action. Encoded by the human endogenous retrovirus envelope gene HERV-W, syncytin-1 trophoblast-specific expression is controlled by epigenetic mechanisms. In non-placental tissues, the syncytin-1 gene is suppressed by hypermethylation in the LTR promoter region. Hypomethylated and activated syncytin-1 gene is found in placental trophoblast lineages and malignant cells. We here demonstrate that while syncytin-1 gene remains silenced in the eutopic endometrium from endometriotic patients, syncytin-1 mRNA and protein are detected in ectopic, endometriotic lesions; particularly the endometrioid glandular endothelial cells. LINE-1 COBRA assay and immunohistochemistry using the 5-MC-specific antibody did not detect any changes in global DNA methylation in the endometriotic tissues. However, results from COBRA and bisulfite sequencing indicated that the LTR region of the syncytin-1 promoter is hypomethylated in endometriotic tissues, highlighting the significance of DNA demethylation in syncytin-1 gene activation. Analysis of DNA methyltransferase 3B (DNMT3B) mRNA levels revealed that DNMT3B3, an isoform carrying methyltransferase activity, is downregulated; whereas DNMT3B7, the isoform without enzymatic activity, is upregulated in the endometriotic tissues, pointing to positive and negative regulatory functions, respectively, of these isoforms on syncytin-1 methylation. These results have provided the first evidence supporting the involvement of epigenetic mechanisms for syncytin-1 upregulation in endometriotic tissues. Considering recent findings on the nonfusogenic activity of syncytin-1, its expression in endometriotic tissues suggests that this multifunctional protein may be implicated in the pathogenesis and/or progression of endometriosis.
Keywords: DNMT3B isoforms